Design Criteria Modeling - Use of Ontology-Based Algorithmic Modeling to Represent Architectural Design Criteria at the Conceptual Design Stage. Issue 4 (3rd July 2016) - Lin, Chieh-Jen
ABSTRACT: This paper proposes an ontology-based parametric modeling tool termed "Design Criteria Modeling (DCM), " which applies a graphic predicate tool and semantic ontologies of architectural topology. DCM aims to help architects in representing, exploring, and validating design criteria by means of parametric 3D model at the early design stage. By applying a semantic ontology reasoner, DCM can help architects to determine whether conceptual models meet the semantic ontology of proposed design criteria. GRAPHICAL ABSTRACT: